Comparison of The Use of Number and Type of Spark Plugs on One Cylinder Gasoline Machine Performance - Fariza, Ahmad; Wonoko, Yuniarto Agus; Ro’isatin, Umi Anis (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2020)
The basic concept of a combustion motor is to convert chemical energy into heat energy and then convert it to mechanical energy. Heat energy is produced from the combustion process between a mixture of fuel and air with a pressure difference triggered by spark (flame). The objective is to determine the difference in power, torque, and average effective pressure by adding the number of spark plugs and using the standard type of spark plug and iridium on a single-cylinder engine. The engine performance testing method uses P-max to get power, while the analysis uses experimental design, the data processing method uses DOE-factorial and the Minitab application 18. Power test for a standard spark plug resulted in 7.93 HP, 0.89 kgm torque and 1207.66 kPa average effective pressure. For iridium spark plug the test produced 9.02 HP, it is 0.91 kg.m for torque and average effective pressure is 1226.32 Kpa. For two standard spark plugs, the power was 9.38 HP, torque was 0.93 kg.m, and the average effective pressure was 1269.96 kPa. Whereas the two iridium spark plugs produced 9.59 HP, 0.91 kg.m torque, and 1277.78 kPa average effective pressure.